STRATEGI PENGEMBANGAN PEMASARAN SAYURAN ORGANIK UNTUK MENINGKATKAN PENJUALAN PADA CV. KURNIA KITRI AYU FARM MALANG - Ignatia, Sari Perwita R; Harianto, Johanes Pungky Dwi; Leu, Norbertus (Fakultas Pertanian, 2024)
The development of organic vegetable marketing strategies is essential for increasing sales and expanding the market reach of these products. The first step is conducting market and consumer analysis to understand consumer preferences and behaviour, as well as identifying potential market segments. Product development should focus on maintaining the quality and consistency and innovating by introducing new varieties or processed products. This research aims to formulate effective marketing development strategies to increase the sales of organic vegetables at CV. Kurnia Kitri Ayu Farm, Malang. The main focus is identifying strengths, weaknesses, opportunities and threats in the marketing development strategy for organic vegetables using SWOT Analysis. The population and sample include the 36 employees and consumers. The research results show that the total score for strengths is 4.48 and the total score for weaknesses is 2.26, giving a total score of 6.74. The total score for opportunities is 4.64 and the total score for threats is 1.51, resulting in a total score of 6.15. The marketing development strategy falls in quadrant I, which involves leveraging opportunities and maximizing existing strengths. The strategy that should be applied in developing the marketing of organic vegetables to increase sales is an aggressive strategy.